V. I. Lenin’s Logical Ideas and Modern Development of Logic - Plečkaitis, Romanas (Problemos, 1970)
The point or departure in V. I. Lenin’s investigation of logical problems is the same as that of G. W. Hegel – dissatisfaction with the then traditional logic. But V. I. Lenin’s arguments for the necessity of constructing the theory of dialectical logic differ from those of G. W. Hegel. Problems of dialectical logic are raised in V. I. Lenin’s works in connection with the philosophical generalizations of achievements of natural science and, on the other hand, in connection with rendering methodological basis for dialectical materialism itself. V. I. Lenin's logical ideas were thoroughly assimilated when mathematical logic gained popularity in our country. It is only with due regard for achievements of the latter that the question of the problems of dialectical logic can be solved. The paper supports the standpoint of those Soviet logicians who take dialectical logic as a metatheory, i.e., science connected with the development of other sciences.